The potential of continuous operating network of space-based radio navigation satellites for weather information retrieval - Yahya, Mohd. Hafiz; Nordin, Zuraidah; Kamaruddin, Md. Nor (2008)
Global Positioning System (GPS) is an emerging satellite-based radio navigation technology for climate analysis and space weather forecasting. The basis for the ground-based GPS atmospheric sensing involves resolving the excess group delay of the GPS signals in terms of the atmospheric parameters using data collected by geodetic-quality GPS receivers at a fixed point on the ground. Given the imperativeness of accurate predictions on the atmospheric profiles in planning a great variety of human endeavours, this paper highlights the establishment of GPS continuously operating reference stations (CORS) network infrastructure for weather information retrieval. In addition to the overviews of the GPS, the principle and the related modelling of GPS ground-based atmospheric sensing, further discussion includes the feasibility of this state-of-the-art technology in substitute of other remote sensing approaches. Based on studies conducted abroad, GPS CORS is sufficiently adequate to augment the analysis of severe weather and relevant environmental issues. In addition to its unprecedented spatial coverage, GPS CORS provides long-term practicality, accuracy and all weather operability for continuous retrieval of the spatial and temporal variability of the Earth's atmosphere.